1990
DOI: 10.1136/oem.47.11.733
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds, respirable dust, and personal factors related to prevalence and incidence of sick building syndrome in primary schools.

Abstract: Possible relations between incidence and prevalence of sick building syndrome (SBS), indoor exposures, and personal factors were studied in a four year longitudinal study among personnel (n = 129) in six primary schools. The The sick building syndrome (SBS) has various nonspecific symptoms such as eye, skin, and upper airway irritation, headache, and fatigue.' Such symptoms are not uncommon in the general population but several studies have shown that these symptoms are more common among people working in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 23 publications
10
132
1
1
Order By: Relevance
“…One phenomenon that may have existed was lower indoor air humidity at higher air exchange rates. In 1990, an experimental study found that moderate steam humidification during the winter reduced the prevalence of throat symptoms, air dryness, and static electricity (Norbäck et al, 1990b). However, this can't be evaluated in this study due to the subtropical climate of Taiwan; steam humidification is not used in winter.…”
Section: Discussionmentioning
confidence: 93%
“…One phenomenon that may have existed was lower indoor air humidity at higher air exchange rates. In 1990, an experimental study found that moderate steam humidification during the winter reduced the prevalence of throat symptoms, air dryness, and static electricity (Norbäck et al, 1990b). However, this can't be evaluated in this study due to the subtropical climate of Taiwan; steam humidification is not used in winter.…”
Section: Discussionmentioning
confidence: 93%
“…Because VOCs are a cause of SBS or MCS, the target VOC concentrations should be minimized. However, it is difficult to specify the target compound, and SBS may actually be a result of compounds [16]. Therefore, to reduce the risks of SBS or MCS, the reduction of not only individual compounds but also total VOC (TVOC) concentrations is very important [17].…”
Section: Discussionmentioning
confidence: 99%
“…These VOCs were selected from previous studies and Korea indoor air quality management act (Norback et al, 1990;Mendell, 2007;Ministry of Environment, 2008). The extraction solvent was carbon disulfide and all extracts were analyzed by gas chromatography (Agilent-6890 Plus; USA) with a flame ionization detector (HP 7683 series autosampler) using a supelco fused silica capillary column (30.0 m/250 μm i.d./1 μm).…”
Section: Analysis For Chemicalsmentioning
confidence: 99%